系統化教學設計：以國中七年級英語寫作教學為例 Instructional System Design: Example of Seventh Grader's Teaching of Writing in the Junior High School - 林婕婷 Lin, Chieh-Ting; 呂正雄Lu, Cheng-Hsiung; 李明憲 Lee, Ming-Shinn (National Changhua University of Education, 2010)
本研究透過系統化教學設計之方式，融合教科書之主要語法結構，發展出適合國中七年級學生的英語寫作教學課程。 本研究得到之研究結論如下： 一、Dick 和 Carey 的系統化教學設計理念，能協助教學者設立明確的教學目標。 二、研究對象填寫之「英語造句書寫興趣量表」前後測，以成對樣本t 檢定分析， 顯示以系統化教學設計英語造句寫作課程，能提升學習者的英語造句書寫興趣。 三、量表中四個分量表－「個人寫作知覺」、「寫作技巧」、「寫作喜好」和「英語學 習態度」之前後測，進行成對樣本t 檢定，分析結果均達顯著差異。 四、以ANCOVA 分析實驗組和控制組的「英語造句書寫興趣量表」前後測，所得結果達顯著差異，顯示此教學方法能提升國中生的英文學習興趣。 This study was based on the theory of Dick and Carey's instructional system design （ISD） to develop the curriculum, and combined the contents of textbook to develop an effective teaching contents for 7th graders in a Junior High school. The procedures were as follows: first, the literature review explored the types and teaching methods of English writing; second, the researchers followed the model to develop the teaching materials; finally, the pretest and posttest evaluations, Writing Interest Questionnaire of Making English Sentences, and student's worksheets were analyzed to see if the teaching contents had impacts on students' learning outcomes. The major results were listed as follows: 1.Based on Dick and Carey's model of instructional system design, the effective teaching contents could be developed. 2.There is significant difference between the pretest and posttest of Writing Interest Questionnaire of Making English Sentences in experiment group to indicate that the designed courses enhanced students' interest in making English sentences. 3.The result of the posttest of the questionnaire was better than that of the pretest in four aspects- "writing consciousness", "writing skills", "writing preference", and "learning attitudes". 4.There is significant difference between experiment group and control group in the pretest and posttest of Writing Interest Questionnaire of Making English Sentences. It indicates that the designed courses enhanced students' interest in learning English.